2017
DOI: 10.1080/03610918.2017.1381740
|View full text |Cite
|
Sign up to set email alerts
|

On quantile residuals in beta regression

Abstract: Beta regression is often used to model the relationship between a dependent variable that assumes values on the open interval (0, 1) and a set of predictor variables. An important challenge in beta regression is to find residuals whose distribution is well approximated by the standard normal distribution. Two previous works compared residuals in beta regression, but the authors did not include the quantile residual.Using Monte Carlo simulation techniques, this paper studies the behavior of certain residuals in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 22 publications
0
18
0
4
Order By: Relevance
“…Additionally, some residual diagnostics are provided in the Appendix using the quantile residuals (Pereira, 2019). These are showing (Figure ) that the model is valid.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, some residual diagnostics are provided in the Appendix using the quantile residuals (Pereira, 2019). These are showing (Figure ) that the model is valid.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of a non-normal regression model for modeling a highly skewed and continuous outcome variable, Scudilio and Pereira (2020) [14] proposed an adjusted quantile residual to diagnose inverse Gaussian or Gamma regression models, which was shown to be a better choice to perform diagnostic analysis compared to traditional residuals. Pereira (2019) [12] and Arenas (2019) [13] investigated the properties of the quantile residual in the beta regression and generalized Johnson S B regression models, respectively. Their results showed that the quantile residual is well approximated by a standard normal distribution.…”
Section: Randomized Quantile Residual Definition Of Randomized Quantimentioning
confidence: 99%
“…For modeling non-normal and continuous outcome data, several studies have investigated the properties of quantile residuals for checking the model fit. For example, Pereira (2019) [12] investigated the properties of the quantile residual in the beta regression model and demonstrated that the distribution of the quantile residual is better approximated by the standard normal distribution than that of the other residuals in most scenarios. Lemonte and Moreno-Arenas (2019) [13] proposed the normalized quantile residual to check the adequacy of the generalized Johnson S B (GJS) regression model, which were shown as a better choice to identify departures from the model assumptions and to assess the overall goodness-of-fit than the deviance residual.…”
Section: Introductionmentioning
confidence: 99%
“…Por se tratar de um método informal para verificar a distribuição da variável resposta, uma grande dificuldade dos gráficos de probabilidade normal e meio normal está em avaliar até que ponto certas irregularidades no padrão linear dos resíduos podem ser consideradas naturais. Além disso, mesmo que o modelo seja correto, os resíduos não são independentes e nem possuem distribuição exatamente normal padrão em amostras finitas (Pereira, 2017).…”
Section: Gráficos De Probabilidadeunclassified